The Results of Work Models Applied During the COVID-19 Pandemic - Kemal Temel; Yener Pazarcık (Istanbul Management Journal)
The aim of this study is to investigate the individual effects and institutional reflections different organizational work models have in terms of employees and to contribute to the field of application and the related literature by explaining their results and effects on work life. The study is based on the phenomenological research design and focuses on the participants’ experiences during the COVID-19 pandemic. The study was carried out using the interview method on a volunteer basis with 16 managers. The data were analyzed using MAXQDA 2020 and evaluated by collecting two main categorical themes and 13 sub-themes. The study observed negative aspects such as the ineffectiveness of face-to-face communication, prolonged communication times, experience transfer and socialization problems, and the intertwining of professional life and social life. Positive results were determined such as a reduction in time and money spent on commuting, work flexibility, having the opportunity to spare more time for oneself and family, and reduced office expenses. The following determinations were made: organizations offer different levels of employee support, practices have no standardization, the problems employees experience are preventable with sufficient organizational support, and legal regulations are needed. The results revealed deficiencies to be present in crisis management, the organizations to be unprepared for the crisis, and all organizations to need to review their processes regarding fringe benefits. The study has aimed to contribute to the literature by focusing on the results of the work models that have been applied during the COVID-19 pandemic.